Electrical characterization of solar sensitive zinc oxide doped-amorphous carbon photodiode - Koc, Mumin Mehmet; Aslan, Naim; Erkovan, Mustafa; Aksakal, Bunyamin; Uzun, Orhan; Farooq, W. Aslam; Yakuphanoğlu, Fahrettin (Elsevier Gmbh, 2019)
A new solar-sensitive zinc oxide doped-amorphous carbon diode was fabricated using the electrochemical deposition technique. The current-voltage characteristics of the fabricated Al/ZnO-a:C/p-Si/Al diode were investigated under dark and various lighting intensities using both I-V and C-V methods. The fabricated diode was characterized by XRD, SEM-EDS, FTIR and XPS analysis. Through the analysis, it was determined that the photocurrents increased with increasing intensity of incident light. The capacitance-voltage (C-V) characteristics revealed that the capacitance of the diode depended on voltage, frequency and illumination, indicating the existence of a continuous distribution of interface states. It was found that the capacitance changed drastically with changing frequency and separation was observed in different frequencies, as identified in the reverse bias region. The ideality factor obtained was found to be higher than unity, with the average barrier height and ideality factor of the diode were found to be 0.528 +/- 0.0069 eV and 5.24 +/- 0.39, respectively. The newly fabricated ZnO-doped amorphous carbon (Al/ZnO-a:C/p-Si/Al) photodiode exhibited good solar sensitivity. The overall results indicated that the fabricated Al/ZnO-a:C/p-Si can be used as a solar sensitive diode in optoelectronic device applications as an alternative to graphene-based materials.
Keywords: ZnO-a:C; Solar sensitive diode; Carbon; Photovoltaic behaviour; Electrodeposition technique